Gambaran Tingkat Pengetahuan Ibu Nifas tentang Infeksi Jahitan Perineum di RSUD Panembahan Senopati Bantul - Kirnantoro Kirnantoro; Nur Indah Rahmawati; Iyoy Siti Muharomah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2014)
Demographic Health Survey Indonesia in 2012, maternal mortality (AKI) is still high 359/100,000 live births, while the target of the MDGs by 2015, AKI can be reduced to 102 per 100,000 live births (SDKI, 2012). The direct cause of maternal mortality in Indonesia is bleeding (28%), eklamsi (24%), infection (11%), birth time (5%) and abort (5%) (Department of Health, 2010). The Purpose of this descriptive quantitative research is to identify the level of knowledge of childbearing mother on perineal suture infection in Panembahan Senopati Hospital, Bantul. This study was conducted at the hospital panembahan senopati bantul on 14-29 June 2014 with 38 samples determined by accidental sampling techniques. Research instrument used in this study was questioner. The result was of 30 respondents unrisk age (78,94%);respondent with the parity more than one children was 23 or 60,52%; mostly respondents were graduated from high school at 23 (60,52%); they were mostly household at 32 people (84,21%); and respondents had good level of knowledge on perineal infection at 26 people (68,42%). Conclusion, postpartum mothers in Panembahan Senopati Hospital have good level of knowledge on perineal suture infection.